Remodeling of Bone Marrow Hematopoietic Stem Cell Niches Promotes Myeloid Cell Expansion during Premature or Physiological Aging - Ho, Ya-Hsuan; del Toro, Raquel; Rivera-Torres, José; Rak, Justyna; Korn, Claudia; García-García, Andrés; Macías, David; González-Gómez, Cristina; del Monte, Alberto; Wittner, Monika; Waller, Amie K.; Foster, Holly R.; et al. (Cell stem cell, 2019)
Hematopoietic stem cells (HSCs) residing in the bone marrow (BM) accumulate during aging but are functionally impaired. However, the role of HSC-intrinsic and -extrinsic aging mechanisms remains debated. Megakaryocytes promote quiescence of neighboring HSCs. Nonetheless, whether megakaryocyte-HSC interactions change during pathological/natural aging is unclear. Premature aging in Hutchinson-Gilford progeria syndrome recapitulates physiological aging features, but whether these arise from altered stem or niche cells is unknown. Here, we show that the BM microenvironment promotes myelopoiesis in premature/physiological aging. During physiological aging, HSC-supporting niches decrease near bone but expand further from bone. Increased BM noradrenergic innervation promotes β2-adrenergic-receptor(AR)-interleukin-6-dependent megakaryopoiesis. Reduced β3-AR-Nos1 activity correlates with decreased endosteal niches and megakaryocyte apposition to sinusoids. However, chronic treatment of progeroid mice with β3-AR agonist decreases premature myeloid and HSC expansion and restores the proximal association of HSCs to megakaryocytes. Therefore, normal/premature aging of BM niches promotes myeloid expansion and can be improved by targeting the microenvironment. [Display omitted] •Reduction of endosteal BM and expansion of non-endosteal BM occurs with age•β2/β3-ARs exhibit opposite and niche-dependent regulation of myelopoiesis•β2-AR overriding β3-AR promotes myeloid expansion during physiological aging•Premature HSC aging in HGPS can be improved by targeting the microenvironment Recent studies have suggested a microenvironmental contribution to stem-cell aging, but the mechanisms are largely unexplored. Méndez-Ferrer et al. report anatomical remodeling of blood-stem-cell-supporting niches and functional switch of β adrenergic signals, leading to myeloid expansion during aging. Targeting the microenvironment can improve pathological, premature, niche-dependent hematopoietic aging in mice.